Identifying Medicare beneficiaries with dementia. Issue 8 (26th April 2021) - Moura, Lidia M. V. R.; Festa, Natalia; Price, Mary; Volya, Margarita; Benson, Nicole M.; Zafar, Sahar; Weiss, Max; Blacker, Deborah; Normand, Sharon‐Lise; Newhouse, Joseph P.; Hsu, John
Abstract: Background/Objectives: No data exist regarding the validity of International Classification of Disease (ICD)‐10 dementia diagnoses against a clinician‐adjudicated reference standard within Medicare claims data. We examined the accuracy of claims‐based diagnoses with respect to expert clinician adjudication using a novel database with individual‐level linkages between electronic health record (EHR) and claims. Design: In this retrospective observational study, two neurologists and two psychiatrists performed a standardized review of patients' medical records from January 2016 to December 2018 and adjudicated dementia status. We measured the accuracy of three claims‐based definitions of dementia against the reference standard. Setting: Mass‐General‐Brigham Healthcare (MGB), Massachusetts, USA. Participants: From an eligible population of 40, 690 fee‐for‐service (FFS) Medicare beneficiaries, aged 65 years and older, within the MGB Accountable Care Organization (ACO), we generated a random sample of 1002 patients, stratified by the pretest likelihood of dementia using administrative surrogates. Intervention: None. Measurements: We evaluated the accuracy (area under receiver operating curve [AUROC]) and calibration (calibration‐in‐the‐large [CITL] and calibration slope) of three ICD‐10 claims‐based definitions of dementia against clinician‐adjudicated standards. We applied inverse probability weighting to reconstruct the eligible population and reported the mean and 95% confidence interval (95% CI) for all performance characteristics, using 10‐fold cross‐validation (CV). Results: Beneficiaries had an average age of 75.3 years and were predominately female (59%) and non‐Hispanic whites (93%). The adjudicated prevalence of dementia in the eligible population was 7%. The best‐performing definition demonstrated excellent accuracy (CV‐AUC 0.94; 95% CI 0.92–0.96) and was well‐calibrated to the reference standard of clinician‐adjudicated dementia (CV‐CITL <0.001, CV‐slope 0.97). Conclusion: This study is the first to validate ICD‐10 diagnostic codes against a robust and replicable approach to dementia ascertainment, using a real‐world clinical reference standard. The best performing definition includes diagnostic codes with strong face validity and outperforms an updated version of a previously validated ICD‐9 definition of dementia.